Rudisantoso Hasil penelitian : PENINGKATAN KEMANDIRIAN SANTRI MELALUI PROGRAM PELATIHAN BERBASIS KOMPETENSI DI PONDOK PESANTREN RAUDLATUL MUTA’ALLIMIN KAMPUNG JAYA TINGGI KECAMATAN KASUI KABUPATEN WAY KANAN - Rudisantoso (Prodi Pengembangan Masyarakat Islam STAIN Teungku Dirundeng Meulaboh, 2022)
This study aims to analyze students' ability to increase independence through competency-based training programs at Work Training Center of Raudlatul Muta'allimin Islamic Boarding School, Jaya Tinggi Village, Kasui District, Way Kanan Regency. The type of research applied is descriptive field research with a qualitative approach. Data sources were targeted and snowballed, including Islamic boarding school heads, Islamic boarding school supervisors and administrators, Islamic boarding school labor training center instructors, students and community leaders. Collecting data using interview, observation and documentation techniques, then the results are analyzed by triangulating sources, techniques and time. The results of the study revealed that: (1) efforts to increase self-reliance through competency-based training programs still need to be further improved, since the training strategies and methods do not yet match the characteristics of alumni, and the lecture method is more widely used, training institutions do not yet match the number of trainees, skills assessment and recruitment are still lacking, the number of training managers does not yet correspond to the large number of trainees, the training activity is more theoretical than practical, the training activities are not carried out on the job, they rarely carry out skills assessment (practice), still do not offer participants opportunities to train for internships in workplaces that provide graphic design services, and do not involve students in graphic design competitions at both regional and national levels. (2) The independence of the students through competence-oriented training programs of the vocational training center still needs to be improved.